Perception of women of the Arthurian legend in the Middle Ages and in the twentieth century - Štefanidesová, Marie (2007)
The dissertation tries to show that while in the Middle Ages the central characters of the Arthurian legend were the male heroes and the females played a rather marginal role, this view changed in twentieth-century rewritings. Writers such as T. H. White or Marion Zimmer Bradley approach the legend in a new way even though White preserves the male point of view as opposed to Bradley, who concentrates on the women and their different perception of the events and heroes